컨조인트 분석을 이용한 체험형 승마관광 선택속성 연구 - 윤여경; Yeo Kyung Yun; 조광민; Kwang Min Cho; 장원용; Won Yong Jang (Ch'eyuk kwahak yŏn'gu, 2017)
[목적] 체험형 승마관광은 관광과 스포츠산업의 확대에 따라 잠재수요가 계속 증가하고 있으나 기대 수요를 충족시키기 위한 체험승마장은 비효율적으로 운영되고 있다. 따라서 본 연구는 승마관광 고객의 승마장 선택속성에 대한 상대적 중요도를 조사하고 실제 시장점유율에 긍정적인 영향을 미치는 요인에 대해 분석하여 국내 승마장 운영 수지를 개선할 수 있는 방안을 모색하고자 하였다. [방법] 이를 위해 제주, 경기, 경북 지역에서 승마체험을 선택한 승마관광객 258명을 대상으로 설문조사를 실시하였으며, 승마장 선택속성의 상대적 중요도를 파악하기 위해 컨조인트 분석과 체험형 승마관광 시장점유율을 예측하기 위한 시뮬레이션을 시행하였다. [결과] 분석 결과 비용이 승마장을 선택하는데 가장 중요한 요인인 것으로 나타났으며 프로그램, 입지, 직원 순으로 중요도가 나타났다. 또한 “승마체험을 10,000원에 제공하면서 이와 함께 즐길 수 있는 다양한 프로그램이 가능하며 도로 상태와 주차시설이 양호하고 전문성을 가진 직원이 배치된 승마장”이 가장 높은 시장점유율을 나타냈다. [결론] 본 연구는 위의 연구결과에 따라 승마장 운영자들에게 효과적이며 효율적인 운영 방안을 제시하였으며 정책적인 시사점에 대해서도 제언하였다. [Purpose] There is a growing number of potential demand on experiential horse riding tourism due to the expand of tourism and sports industries, however the experiential horse riding clubs are operating inefficiently. Therefore the purpose of this study is to investigate implicity importance of horse riding club’s selection attributes and analyze factors affecting positive effect on market share thereby find the way to improve operating system. [Methods] The survey was done among 258 horse riding tourism customers of Jeju, Gyeonggi, and Gyeongbuk provinces, and conjoint analysis to figure out the relative importance of selection attributes, and simulation to predict the market share of experiential horse riding were conducted. [Results] The results are as follows. Cost was the most important factor when selecting horse riding club and program, location, staff were followed by. Also, “The club that serves various activities with horse riding program at 10,000won where the condition of road and parking lot are good” had the best market share. [Conclusion] This study suggested the effective and efficient manners to operate the horse riding club and the political implication.